Plant retromer, localized to the prevacuolar compartment and microvesicles in arabidopsis, may interact with vacuolar sorting receptors - Oliviusson, Peter; Heinzerling, Oliver; Hillmer, Stefan; Hinz, Giselbert; Robinson, David G. (The plant cell, 2006)
Receptors for acid hydrolases destined for the lytic compartment in yeast and mammalian cells are retrieved from intermediate, endosomal organelles with the help of a pentameric protein complex called the retromer. We cloned the Arabidopsis thaliana homologs of the three yeast proteins (Vps35, Vps29, and Vps26) constituting the larger subunit of retromer and prepared antisera against them. With these antibodies, we demonstrated the presence of a retromer-like protein complex in salt extracts prepared from Arabidopsis microsomes. This complex is associated with membranes that coequilibrate with prevacuolar compartment markers and with high-density sedimenting membranes. Immunogold negative staining identified these membranes as 90-nm-diameter coated microvesicles. Confocal laser scanning immunofluorescence studies performed on tobacco (Nicotiana tabacum) BY-2 cells revealed high degrees of colabeling between all three retromer antisera and the prevacuolar compartment (PVC) markers PEP12 and vacuolar sorting receptor VSRAt-1. The presence of plant retromer at the surface of multivesicular bodies was also demonstrated by immunogold labeling of sections obtained from high-pressure frozen/freeze-substituted specimens. Treatment of BY-2 cells with wortmannin led to swelling of the PVC and a separation of the VPS35 and VSR signals. Preliminary data suggesting that retromer interacts with the cytosolic domain of a VSR were obtained by immunoprecipitation experiments performed on detergent-solubilized microsomes with Vps35 antibodies.